Perception of public about early marriage based on education level - Ika Sandra Dewi; Daharnis Daharnis; Syahniar Syahniar (Fakultas Ilmu Pendidikan UNP)
Public perception of early marriage has many variations. The education level is factors which influence it. Aims of this research are to description’s differences public perception of early marriage based on education level. The method was ex-post facto with a threedesign. The population is the community of Sidojadi, Kecamatan Bukit Malintang, Kabupaten Mandailing Natal, consists of 888 people and samples were 276 people. The instrumentis a perception of public about early mirage by using Likert scale model andreliability test is 0.910. Data were analyzed by using the descriptive statistics and ANOVA. The result of this research shows that there is a significant difference of public perception about early marriage based on the education level.